Evaluasi Program Pembinaan Olahraga Futsal Pada Ekstrakurikuler Futsal SMAN 1 Dolopo Kabupaten Madiun - Santoso, Muhammad Naufal Anditya; Wahyudi, Heri; Widodo, Achmad; Wismanadi, Himawan (Universitas Singaperbangsa Karawang, 2024)
Sports coaching plays an important role in improving achievements in the world of sports, because developments in the world of sports are greatly influenced by such coaching. SMAN 1 Dolopo is also involved in the process of sports coaching, including in the sport of futsal, which is followed by students through extracurricular activities. The purpose of this study was to evaluate the futsal extracurricular coaching program at SMAN 1 Dolopo. The method applied to the research process was carried out by applying the CIPP evaluation method developed by Stuffbleam, which includes aspects of Context, Input, Process, and Product. This approach allows a comprehensive analysis of various elements, ranging from context, input, process, to product. This research uses a mixed method approach by utilizing various data collection techniques, such as observation, questionnaires, interviews, and documentation. The subjects of this research were parties related to the futsal extracurricular at SMAN 1 Dolopo, including administrators, coaches, and athletes. The results of this study state that the coaching aspect has been running well, it can be seen from the results that have been achieved and also the coordination between coaches and extracurricular administrators. The input aspect in the recruitment process of futsal athletes needs to be improved by periodically introducing extracurricular activities and for the coach already has a good capacity, in terms of infrastructure the management must care about which is classified as incomplete because the facilities here are the main support.